Identification of selective mtbDHFR inhibitors by virtual screening and experimental approaches. (21st January 2022) - He, Juan; Li, Cong; Hu, Wei; Li, Chungen; Liu, Song; Sui, Jing; Zhang, Tianyu; Sun, Qingxiang; Luo, Youfu
Abstract: mtb DHFR‐targeting inhibition has become a promising approach for tuberculosis treatment. In the current research, a multi‐step virtual screening effort toward ZINC and MCE databases was devoted to discover novel mtb DHFR inhibitors. Based on binding affinity of small molecules through molecular docking study in AutoDock Vina, the number of compounds was reduced to 952, 688. Further, these compounds were employed by a step‐by‐step multiple docking programs of Schrödinger suite and filtered by pharmacokinetics and PAINS parameters. Finally, nine ZINC compounds and 400 MCE compounds were obtained. These compounds of binding ability were tested with mtb DHFR by FluoPol‐ABPP approach established in this work. Finally, AF‐353 compound was found to have strong binding effect to mtb DHFR. AF‐353 was further tested for mtb and h DHFR enzymatic activities, and it was proved to possess 50‐fold selectivity toward mtb DHFR over h DHFR. In silico MD simulation results supported this selectivity. Abstract : A highly selective mtbDHFR inhitor was identified by combinational approaches of multiple virtual screening and wet experiments.